Housing Capital Resource and Representation - Lanzinger, Margareth (European History Yearbook, 2017)
Throughout history, houses have been an economic resource as much as a means of social, political and cultural agency. From the early modern period to the 20th century, the multifaceted capital of houses linked individuals, families and societies in specific ways. The essays collected here probe the material texture of past societies concerning the inheritance, value, sale or maintenance of houses as well as their symbolic meanings.